DESIGNING A HIGH ENGAGED AND PERFORMING ORGANISATION WITH A FOCUS ON DEVELOPING LEADERSHIP, STRUCTURE, AND NON-MONETARY REWARDS TO ENHANCE EMPLOYEE WORK ENGAGEMENT AND EMPLOYEE JOB PERFORMANCE: A CASE STUDY AT AA GROUP CO., LTD, MANDALAY, MYANMAR - Phyu, Hsu; Dowpiset, Kitikorn (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2022)
This action research paper emphasizes the change in organisation design elements consisting of leadership, structure, and non-monetary rewards enhancing employee work engagement and employee job performance at AA Group Co., Ltd; a family-owned gold business group located in Mandalay division, Myanmar. The company has 450 manpower and is planning to develop its human capitals and restructure its business towards IPO. The survey research and ODIs are targeted employees working from different management levels at the focal company. The actual quantitative sample size is determined as 124 and the actual qualitative sample size is determined as 15. This research utilizes both quantitative and qualitative research methods within its action research framework in order to analyse and compare the situation at the focal company in both pre-ODI and post-ODI stages. This research paper accesses the initial impacts of ODIs on the leadership, structure, non-monetary rewards, employee work engagement, and employee job performance at AA Group Co., Ltd. Based on theoretical, conceptual frameworks, ODI results, there is an improvement of desired variables at AA Group Co., Ltd. This research paper also proposes a three-year logical framework (action plan) to have a sustainable development on the recent improvement of tested variables at AA Group Co., Ltd.